Prospective pilot study of anorectal fistula closure with the OTSC Proctology - Proßt, Rüdiger Lothar; Bussen, Dieter G. (Colorectal disease, 2015)
Aim The OTSC Proctology is a surgical device for anorectal fistula closure. It consists of a super-elastic nitinol clip, which is placed (with the aid of a transanal applicator) on the internal fistula opening to achieve healing of the fistula track. A prospective, two-centre clinical pilot study was undertaken to assess the efficacy and safety of the OTSC Proctology in patients with a complex high anorectal fistula. Method In patients with a complex anorectal fistula the primary track was debrided using a special brush and the clip was applied to the internal fistula opening. After 6 months the postoperative clinical course and fistula healing were assessed. Results Twenty patients with a cryptoglandular anorectal fistula (14 with a transsphincteric fistula and six with a suprasphincteric fistula) were included in the study. There were no intra-operative technical or surgical complications. Postoperatively no patient reported intolerable discomfort or a sensation of a foreign body in the anal region. At 6 months after surgery, 18 (90%) patients had no clinical signs or symptoms of fistula and were considered healed, whereas in two the fistula persisted. In 13 (72%) of these 18 patients, the clip was still in place without causing problems, whereas in three patients the clip had spontaneously detached. In the two remaining patients it was necessary to remove the clip due to discomfort and delayed wound healing. Conclusion Anorectal fistula closure with the OTSC Proctology is an innovative, sphincter-preserving minimally invasive procedure with promising initial results and a high rate of patient satisfaction.